Differences in p53 Expression in High-Grade Conventional Osteosarcoma and Giant Cell Tumor of Bone - Teguh Prihantoro; Eviana Norahmawati; Rose Khasana Dewi; Holipah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Osteosarcoma is the most common primary tumor of bone. Generally, patients with osteosarcoma have a poor prognosis. So it is very important to be able to diagnose as early as possible. Histopathologically, osteosarcoma has a variety of types similar to non-malignant lesions, such as giant cell tumor of bone. Therefore, caution is needed in diagnosing because if it is misdiagnosed, it will result in different management. This study aims to look at differences in p53 protein expression in high-grade conventional osteosarcoma and giant cell tumor of bone. Methods: This observational analytic study used 30 samples from tissue biopsies/surgeries diagnosed with conventional high-grade osteosarcoma and 30 samples of giant cell tumor of bone at the Anatomical Pathology Installation of Dr. Saiful Anwar General Hospital Malang, Indonesia, between 2018-2022. p53 expression was examined using the immunohistochemical staining method. Positive if stained with brown on the nucleus of the cell, the percentage of 500 malignant cells was calculated in the large field of view of the objective lens (x40) randomly. Univariate and bivariate data analysis was performed using SPSS. Results: The average p53 protein expression in conventional high-grade osteosarcoma was 80.0% ± 26.2, with the lowest value being 19% and the highest value being 100%. Whereas in giant cell tumor of bone, the average p53 expression was 1.7% ± 4.3, with the lowest value being 0% and the highest value being 17.6%. Statistical analysis using the Mann-Whitney test showed that p53 expression in conventional high-grade osteosarcoma and giant cell tumor of bone showed a significant difference (p=0.000). Conclusion: There is a significant difference between p53 expression in high-grade conventional osteosarcoma and giant cell tumor of bone.